2007
DOI: 10.1080/14017430601187124
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin induced sustained anti–adrenergic actions in guinea pig heart muscle involves PKC

Abstract: Anti-beta-adrenergic effects of bradykinin on contractile force and action potential duration were demonstrated. PKC was important for the sustained effect on contractile force, but not for the acute effect and the effect on action potential duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Bradykinin also competes with adrenergic stimulation of the heart. 16 Our rabbit cardiomyocytes have surprisingly high basal adenylyl cyclase activities, resulting in a futile cycling of cAMP synthesis and breakdown in these quiescent cells. This basal adenylyl cyclase activity is reflected in the rise in cAMP when the major PDEs were inhibited with the PDE inhibitor cocktail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bradykinin also competes with adrenergic stimulation of the heart. 16 Our rabbit cardiomyocytes have surprisingly high basal adenylyl cyclase activities, resulting in a futile cycling of cAMP synthesis and breakdown in these quiescent cells. This basal adenylyl cyclase activity is reflected in the rise in cAMP when the major PDEs were inhibited with the PDE inhibitor cocktail.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiomyocyte hypothesis of preconditioning would be disproved if it could be shown that one or more of the receptors used by IPC's signaling are not expressed by the cardiomyocyte. Adenosine A 1 AR stimulation markedly inhibits isoproterenol (iso)-induced increase in contractility 15 as does bradykinin, 16 indicating that both of those receptors coexist with adrenergic receptors on cardiomyocytes. It has been more difficult to demonstrate the presence of the remaining receptors.…”
Section: Introductionmentioning
confidence: 99%